Anti-aging and anti-microbial effects of melleolide on various types of yeast. Issue 3 (4th March 2014) - Nakaya, Shigeru; Kobori, Hajime; Sekiya, Atsushi; Kawagishi, Hirokazu; Ushimaru, Takashi
Abstract: The chronological lifespan (CLS) of the budding yeast Saccharomyces cerevisiae is a model for the aging of post-mitotic cells in higher eukaryotes. In this study, we found that the sesquiterpene aryl ester melleolide expands the CLS of budding yeast. In contrast, melleolide compromised the CLS of the fission yeast Schizosaccharomyces pombe . This indicates that melleolide might have a potential anti-aging activity against some types of cell, and that it might be useful as a selective anti-fungal drug.